2021
DOI: 10.3390/jmse9040415
|View full text |Cite
|
Sign up to set email alerts
|

Decarbonization in Shipping Industry: A Review of Research, Technology Development, and Innovation Proposals

Abstract: This review paper examines the possible pathways and possible technologies available that will help the shipping sector achieve the International Maritime Organization’s (IMO) deep decarbonization targets by 2050. There has been increased interest from important stakeholders regarding deep decarbonization, evidenced by market surveys conducted by Shell and Deloitte. However, deep decarbonization will require financial incentives and policies at an international and regional level given the maritime sector’s ~3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(83 citation statements)
references
References 83 publications
0
37
0
1
Order By: Relevance
“…Several experimental results available in the literature concluded that a 100% ammonia fuel mode (i.e., . E diesel = 0) leads to performance problems in compression ignition engines because ammonia has a high resistance to autoignition [25,26]. According to this, the power contribution from diesel fuel analyzed in the present work encompasses the range from 10 to 100%.…”
Section: Resultsmentioning
confidence: 94%
“…Several experimental results available in the literature concluded that a 100% ammonia fuel mode (i.e., . E diesel = 0) leads to performance problems in compression ignition engines because ammonia has a high resistance to autoignition [25,26]. According to this, the power contribution from diesel fuel analyzed in the present work encompasses the range from 10 to 100%.…”
Section: Resultsmentioning
confidence: 94%
“…Ammonia can be used as a drop-in fuel in diesel in internal combustion engines and gas turbines and as a primary fuel in fuel cells, making it a very appealing and competitive alternative [6,18,23]. However, as Imhoff et al suggest in their study, "naval vessels are less likely to adopt ammonia powertrains without significant redesigns" [29].…”
Section: Ammonia In Various Technologiesmentioning
confidence: 99%
“…Furthermore, fuels such as LNG can have a negative impact on the environment due to "methane slip." Methane is a much more potent greenhouse gas than CO 2 [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy transition towards lowcarbon energy calls for a changeover period, meaning gradual decarbonization through gasification [1,2] (in the first stage) followed by reducing the use of fossil fuels (coal, oil, gas) in favor of renewable energy sources such as wind, solar energy, biomass and biogas (in the second stage). At this point, it is worth emphasizing that decarbonization is a broad concept and applies not only to energy [3], but also technology [4][5][6][7][8], economy and politics [9][10][11][12]. It is believed that within the next decade or two the use of natural gas for the production of electrical energy in Poland will increase.…”
Section: Introductionmentioning
confidence: 99%